(untitled) (EAAE Annual Conference Proceedings, 2023)
The paper questions to what extent architectural research can act as tool to subvert power relations and to enable the critique of capitalism that, according to Meiksins Wood “requires a constantly renewed critique of the analytic instruments designed to understand it”.